PERAN PENGENALAN SISTEM PEREKONOMIAN SYARIAH TERHADAP PERKEMBANGAN EKONOMI SYARIAH DI INDONESIA - Oveliana Puspitasari; Fauzatul Laily Nisa (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to explore information regarding the role of the introduction of the sharia economic system on the development of the sharia economy in Indonesia using a literature study research method involving the process of collecting relevant data related to research topics from various sources, academic books, scientific articles, research reports and theses. . The results of this research explain that the implementation of the Sharia economic system in Indonesia has received a positive response from the public and has also had a positive impact on economic development in Indonesia. However, knowledge regarding Sharia economics itself is not yet fully known by the wider community.